Money in the Roman Empire from Hadrian to the Severi: A study of attitudes and practice - Haklai, M (2013)
The present study offers an in-depth examination of the institutional framework within which money operated as an economic agent in the Roman empire. Analyses focus on Classical Roman Law as reflected in the writings of Roman jurists from the second and early-third centuries CE. The legal sources are augmented by documentary materials, which give independent, albeit sporadic, evidence for actual practice. The thesis follows current trends in economic history to adopt approaches advanced by New Institutional Economics (NIE), while generally accepting Keynesian claims for the endogenous nature of money. Its innovative contribution is in suggesting a complexity-oriented approach to modelling the behaviour of money in the Roman empire; seeing money as a complex economic phenomenon, i.e. as a diverse and manifold apparatus which allows for new patterns of activity to be created by individuals, who self-adjust their use of it to the continuously evolving system in which they operate. The thesis is divided into four parts. The first is introductory. The second concerns the legal institutional framework for economic interaction; with discussions generally organised according to Roman legal categorisation, and considers developments in the role allocated to money in legal definitions for exchange transaction. The third part examines two study-cases of money-related institutions, namely, the instrument of interest, and interest-bearing deposits, demonstrating how money stimulated the interconnected dynamics within and between legal traditions operating under Roman regime. The fourth and last part is dedicated to a more general analysis of the complex nature of Roman money, attempting to model the historical example of Roman money with the help of complexity-oriented visualisations.